First record of paralytic shellfish toxins in marine pufferfish from the Spanish Mediterranean coast using cell-based assay, automated patch clamp and HPLC-FLD - Alkassar, Mounira; Tudó, Àngels; Rambla-Alegre, Maria; Ferreres, Laura; Diogène, Jorge; Sureda, Francesc X.; Campàs, Mònica (Chemosphere (Oxford), 2024)
Pufferfish is one of the most poisonous marine organisms, responsible for numerous poisoning incidents and some human fatalities due to its capability to accumulate potent neurotoxins such as tetrodotoxins (TTXs) and paralytic shellfish toxins (PSTs). In this study, tissue extracts (muscle, skin, liver, intestinal tract and gonads) obtained from sixteen pufferfish specimens of the Lagocephalus lagocephalus and Sphoeroides pachygaster species, collected along the Spanish Mediterranean coast, were analysed for the presence of voltage-gated sodium channel (also known as Nav channel) blockers using cell-based assay (CBA) and automated patch clamp (APC). No toxicity was observed in any of the S. pachygaster specimens, but toxicity was detected in the liver of most L. lagocephalus specimens. Instrumental analysis of these specimens, as well as in one Lagocephalus sceleratus specimen, by high-performance liquid chromatography coupled to fluorescence detection (HPLC-FLD) was performed, which confirmed the presence of PSTs only in L. lagocephalus specimens. This analysis reported the presence of saxitoxin (STX) and decarbamoylsaxitoxin (dcSTX) in all positive samples, being dcSTX the major analogue. These results demonstrate the ability of this species to accumulate PSTs, being the first report of the presence of PSTs in Mediterranean L.lagocephalus specimens. Furthermore, the presence of high PSTs contents in all five tested tissues of one L. lagocephalus specimen pointed the risk that the presence of this toxic fish in the Mediterranean Sea may represent for seafood safety and human health in case of accidental consumption. [Display omitted] •CBA and APC were used to assess the presence of PSTs in different pufferfish species.•No toxicity was observed in S. pachygaster.•Toxicity was detected in the liver of most L. lagocephalus.•HPLC-FLD analysis confirmed the presence of PSTs in L. lagocephalus.•STX and dcSTX were detected in all positive samples, being dcSTX the major analogue.